Growth Performance of Layang (Scad) Fish (Decapterus russelli, Ruppell 1830) Caught from Tomini Bay, Indonesia - Abdul Hafidz Olii; Elena Wonneberger; Nuralim Pasisingi (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2022)
Regarding exploitation and optimizing fisheries resources management in Tomini Bay, the Layang scad fish (Decapterus russelli, Ruppell 1830) is one of the small pelagic fishes inhabiting the bay that still lacks biological information. The species becomes the main target commodity for local fishers as it is commonly consumed as a protein source for coastal communities. This study aimed to determine the length-weight relationships and the growth pattern of Layang fish caught by fishers from Tomini Bay. The samples were collected once per month at Gorontalo City Fish Landing Spot from April to June 2020. Tomini Bay was confirmed as the fishing ground of all the landed fish. Layang is caught by Mini purse seines with a minimum mesh size of ¾ inch. A total of 896 samples of Layang fish were collected randomly from the fishers' catch during their unloading activity at the landing site. Abdomen dissection was performed on all samples for determining the fish’s sex. The fish samples' total length and body weight were measured using a ruler (nearest = 1 mm) and a scale (nearest = 0.01 gram). The result revealed that the length-weight equation of male Layang was W = 0.000004 L3.1972 (R2 = 97.57%), and that of female was W = 0.0000007 L3.0613 (R2 = 98.99%). This result implied a positive allometric growth pattern, excluding the females in April 2020.